Causes of differential behavior of extractives on the natural cold water durability of the welded joints of three tropical woods. Issue 12 (18th June 2022) - Eyinga Biwôlé, Jean Jalin; Biwolé, Achille Bernard; Zobo Mfomo, Joseph; Segovia, César; Pizzi, Antonio; Chen, Xinyi; Fedoung Fongnzossie, Evariste; Ateba, Atangana; Meausoone, Pierre-Jean
Abstract: This study aims to investigate the causes of the differential behavior of extractives on the water resistance of the welded joints of three tropical woods. The welded joints of these chemically characterized woods were obtained by rotational dowel welding. The respective extractives contents obtained during the successive extractions were 12.98 ± 0.90% for Iroko, 17.36 ± 0.40% for African pearwood and 18.16 ± 1.00% for Padauk. Phytochemical screening revealed a high concentration of polyphenols in the extractives of Padauk and Iroko compared to African pearwood. The highest delamination rate (76.66%) was obtained with African pearwood. The highest tensile strength before (4.09 MPa) and after (1.94 MPa) the delamination test was obtained with Padauk. MALDI-TOF mass spectrometry analysis revealed non-leaching after 30 days in cold water of lignin and hemicelluloses fragments from Padauk at 536 Da and 698 Da, but just for hemicelluloses fragments as shown by a glucose pentamer at 837 Da, a glucomannan fragment, and of a glucose pentamer with a xylose residue attached at 970 Da that disappeared completely after 30 days of African pearwood water immersion. However, cold water immersion of Iroko appears to remove resveratrol at 250 Da, a stilbene, as well as multiprotonated stilbene at 256 Da while other stilbene class polyphenols such as geranyl trihydroxy stilbene at 364 Da and chlorophorin at 379 Da seem unaffected by water. SEM analysis confirmed perfect adhesion of Padauk and Iroko joints which indicates a strong correlation between the water resistance of the welded joint and the type of extractives.